Mistisisme dalam Perspektif Filsafat Analitik: Antara Wittgenstein dan Mehdi Ha'iri Yazdi - M. Hidayatullah S. (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Language is a principal instrument for philosopher and as a medium for analysis and reflection. Wittgenstein said, that the order analytical philosophy is to clean away the epistemology from the